Interview: JAPKE – The Female Viking Power-house of Lejre - Christine Sonne-Jensen (EXARC Journal, 2019)
Jutta Eberhards has been working with drama and living history for over 30 years. Born in the Friesland district in Germany, Jutta has over the years become a power-house in the management group of Sagnlandet Lejre – The Land of Legends (www.sagnlandet.dk). She has been tirelessly working to uphold the standards of the educational method that she and her colleagues developed: Teacher in role and Presenter in role. In character as a Viking, Jutta inhabits the role of Japke, a völva and Viking woman. In this work, Jutta showed courage and open-mindedness in developing reenactment as a pedagogical and educational method, at a time when this was still relatively unknown in Danish museums and historical centres. Since then, the work of Jutta and her colleagues has inspired other historical institutions to take on living history and reenactment – in historical character and costumes – as an essential part of the presenter’s tools, either following the Lejre method directly or finding inspiration for developing methods of their own.